Austrian Lives - Bischof, Günter (Contemporary Austrian Studies, 2012)
The writing of lives is always situated between fact and fiction, ascertainable data and the imagination of the biographer. Using a variety of biographical techniques, Austrian Lives offers a fascinating cross-section of recent Austrian experience. A major focus of this collection is Austrian intellectual and political figures through the twentieth century. Volume 21 presents an array of political lives, including portraits of Ignaz Seipel and Therese Schlesinger-Eckstein. The essay "Lives of the Mind" offers perspectives of intellectuals in pre- and post-World War II Vienna such as Viktor Frankl and Eugenie Schwarzwald. These more traditional biographies are complemented by studies of ordinary Austrians in wartime Vienna. Accounts of the lives of soldiers, prisoners of war, and farming families provide insight into often overlooked perspectives, while creating a more complete picture of recent Austrian history.